2006
DOI: 10.1179/174328606x151033
|View full text |Cite
|
Sign up to set email alerts
|

Injuries associated with continuous miners, shuttle cars, load–haul–dump and personnel transport in New South Wales underground coal mines

Abstract: In the three years to June 2005, 959 injuries associated with continuous miners (CMs), shuttle cars (SCs), load-haul-dump and personnel transport (PT) were reported by NSW underground coal mines, comprising 23% of all injuries reported. The present paper reports an analysis of the narrative field accompanying these reports to determine opportunities for controlling injury risks. The most common combinations of activity and mechanism were: strain while handling CM cable (96 injuries); caught between or struck b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…A previous analyses of injuries associated with a subset of underground coal mining equipment types has been reported [3]. This paper extends the analysis to include all equipment types, and utilises data from the three years to the end of June, 2008.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…A previous analyses of injuries associated with a subset of underground coal mining equipment types has been reported [3]. This paper extends the analysis to include all equipment types, and utilises data from the three years to the end of June, 2008.…”
Section: Introductionmentioning
confidence: 96%
“…These reports included injuries of varying severity, from medical expenses only, to time lost, and serious bodily injury. Narratives describing the injuries occurring underground were manually coded for equipment involvement; activity being undertaken by the injured person immediately prior to the injury; the injury mechanism; and agent of injury, using previously determined codes [3]. Frequencies of cross-tabulated combinations of codes were calculated and presented graphically to aid interpretation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Ruff et al reported that 41% of severe injuries across all US mines from 2000 to 2007 were associated with machinery [1]. This proportion may be even higher in some sectors: While Burgess-Limerick and Steiner reported that 46% of injuries in New South Wales underground coal mines from 2006 to 2008 were associated with equipment [2]; Cooke et al [3] reported that 68% of injuries at surface coal mines in NSW from 2005 to 2009 were associated with the operation or maintenance of mobile mining equipment. In terms of the types of equipment most frequently associated with injuries, Cooke et al further reported that Haul Trucks (32%) and Bulldozers (21%) were involved in slightly over half of the mobile equipment-related injuries logged at the surface coal mines.…”
Section: Introductionmentioning
confidence: 99%
“…Errors in the operation of roof bolters have caused many fatalities and injuries. Injuries caused by intentional control operation can be divided into the following categories: the wrong control was operated; the correct control was operated in the wrong direction; the intended control was operated in the intended direction while the injured employee (a roof bolter operator or another person) was in a position of danger (Burgess-Limerick, Krupenia, Zupanc, Wallis, & Steiner, 2010;Burgess-Limerick & Steiner, 2006, 2011.…”
Section: Introductionmentioning
confidence: 99%